Empirical Analysis of Operating Efficiency and Firm Value: A Study of Fast Moving Consumer Goods and Pharmaceutical Sector in India - Bhullar, Pritpal Singh (International Journal of Economics and Financial Issues, 2017)
The present paper investigates the impact of operating efficiency on firm valuation for two economic sectors FMCG and Pharmaceutical Sectors in India. The study considers 30 Indian firms from the period of 2005 to 2015. To examine the effect, six financial ratios are considered as proxy for operating efficiency and enterprise value as proxy for Firm value. We employ Panel data analysis to explore the relationship of dependent and independent variable. The results report that Fixed Asset Turnover Ratio (FATO) and Net Profit Margin (NPM) indicates negative relation with Enterprise Value (EV) in Pharmaceutical sector and EV/Sales and Fixed Asset Turnover Ratio (FATO) confirms negative relation with EV for FMCG Sector. The empirical results will act as guidelines for the valuation analysts for implication of new valuation variables by replacing conventional variables. Moreover, the study implies that value creation is more significant to current performance as compared to past performance. Keywords: Operating efficiency, Panel Data, Enterprise value, FMCG and Pharmaceutical Sector JEL Classification: G32, M41